Lazy model generation for implementing efficient theorem provers - Hasegawa, Ryuzo; Koshimura, Miyuki; Fujita, Hiroshi (1992)
Abstract: "This paper presents a new method called lazy model generation for implementing efficient theorem provers. The tasks of theorem proving based on model generation are the generation and testing of atoms that will be members of a model. The generation process tends to fall into combinatorial explosion which makes it difficult to obtain proofs. Lazy model generation is a method aimed at avoiding an over generation of atoms that are irrelevant and unnecessary for obtaining proofs. In fact, without serious consideration of laziness in producing and retaining information of any kind, theorem proving for hard problems would never succeed with a [sic] limited computational resources
Keywords: Automatic theorem proving; KL1 (Computer program language)